2011
DOI: 10.1371/journal.pone.0021804
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Mutagenesis of Xanthomonas axonopodis pv. citri Reveals Novel Genetic Determinants and Regulation Mechanisms of Biofilm Formation

Abstract: Xanthomonas axonopodis pv. citri (Xac) causes citrus canker disease, a major threat to citrus production worldwide. Accumulating evidence suggests that the formation of biofilms on citrus leaves plays an important role in the epiphytic survival of this pathogen prior to the development of canker disease. However, the process of Xac biofilm formation is poorly understood. Here, we report a genome-scale study of Xac biofilm formation in which we identified 92 genes, including 33 novel genes involved in biofilm f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 67 publications
(167 reference statements)
5
96
0
4
Order By: Relevance
“…Surprisingly, XAC2583/gumD showed not only impairment in sliding motility, but also that its ability to swim was affected. In a previous biofilm screening (Li & Wang, 2011b), this mutant was also found to have shortcomings in both types of motilities, confirming our results. We observed that the production of EPS is affected in XAC1260, XAC0533 and XAC2301 (data not shown), although these genes are not known to be related with xanthan synthesis.…”
Section: Biofilm-defective Mutant Affected In Motilitysupporting
confidence: 91%
See 3 more Smart Citations
“…Surprisingly, XAC2583/gumD showed not only impairment in sliding motility, but also that its ability to swim was affected. In a previous biofilm screening (Li & Wang, 2011b), this mutant was also found to have shortcomings in both types of motilities, confirming our results. We observed that the production of EPS is affected in XAC1260, XAC0533 and XAC2301 (data not shown), although these genes are not known to be related with xanthan synthesis.…”
Section: Biofilm-defective Mutant Affected In Motilitysupporting
confidence: 91%
“…These genes are involved in xanthan production (gumB, galU and gumD) (Guo et al, 2010;Li & Wang, 2011b;Rigano et al, 2007), in amino acid metabolism (sahH) (Li & Wang, 2011b) and in periplasmic glucan biosynthesis (hrpM) (Malamud et al, 2012).…”
Section: Characterization Of the Novel And Known Genes Related To Xccmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study based on the in planta analysis of Xac pathotype A mutants has led to the identification of 44 mutated genes in strains that show total or partial inability to induce the Xac virulence phenotype in the host plant [14]. Another study involving the same organism described 292 mutants showing a massive reduction in virulence phenotypes [15]. More recently, seven new genes associated with virulence in X. citri subsp.…”
Section: Introductionmentioning
confidence: 99%